Estimating and Calibrating MFMod : A Panel Data Approach to Identifying the Parameters of Data Poor Countries in the World Bank's Structural Macro Model - Burns, Andrew; Jooste, Charl (World Bank, Washington, DC, 2019)
This paper summarizes the World Bank's approach to identifying parameters for key equations in its macro structural model for countries where short sample sizes or major structural changes render traditional time-series approaches infeasible or yield unstable estimates. To identify parameters that could be used in such cases, a cointegrating panel approach is followed that yields a common long-run estimate of parameters for key equations (to test the theoretical restrictions imposed in the model) and short-run disequilibrium estimates that vary by country. This approach is preferred to pure calibration or Bayesian estimation, because the functional forms imposed in the panel are consistent with those used in the macro structural model.